Analysis of Rare Earth Metal Potential of Parmonangan Area Using X-Ray Fluorescence - Rita Juliani; Rahmatsyah; Togi Tampubolon; Erni Halawa; Silvia Dona Sari; Ismayana; Rama Yana Purba (Postgraduate, University of Mataram, 2025)
Rare Earth Elements (REEs) are strategic commodities essential for various high-technology applications, including renewable energy, electronics, and defense systems. However, their uneven global distribution and increasing demand have intensified the need for exploration in undercharacterized regions. This study investigates the REE potential of weathered granitic rocks in the Pamonangan Sub-district, North Sumatra. A total of 200 mesh rock samples from outcrop and subsurface locations were analyzed using X-Ray Fluorescence (XRF) to determine their elemental composition. The geochemical results show high concentrations of SiO₂ and Al₂O₃ relative to Fe₂O₃, suggesting significant weathering of the granitic parent rocks. The combination of elevated SiO₂ and low P₂O₅ contents indicates a predominance of silica-hosted REE phases over phosphate-hosted minerals. Mineralogical analysis confirms the presence of cassiterite, chlorite, monazite, and zircon as secondary REE carriers, particularly of Ce and La. These findings point to a previously unrecognized potential for REE mineralization in the region. This research provides a geochemical and mineralogical framework for future exploration and highlights the importance of weathered granitoids as prospective REE sources in Indonesia.